Pelatihan Digital Marketing pada Penerbit CV Pena Persada - Wiwit Kurniawan; Fiqoh Afriliani; Soffi Soffiatun; Lukman Hakim; Tri Hidayati (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
ABSTRACTThis community service (PKM) is located at the publisher of CV Pena Persada which aims to introduce the concept of digital marketing to the marketing management system at CV Pena Persada. CV Pena Persada publishers have problems in the form of low book sales and lack of digital-based marketing management. The management of CV Pena Persada publishers has not been able to maximize the various features provided in the digital era. For this problem, the service team provided material on the basics of Digital marketing and how to practice it to increase book sales. The method used in this activity is to use seminars to deliver material about digital marketing. Digital marketing is a sales system that utilizes digital technology such as websites, search engine optimization, digital advertising, and various other things related to the digital world. One of the techniques that can be used in internet marketing is to use websites and online platforms, search engine optimization, and digital paid advertising such as Google AdSense. The result of this PKM is that 80% of the staff and employees at Persada publishers have adequate knowledge about Digital marketing. In addition, 90% of participants also stated that they were satisfied with the material presented. This seminar was attended by 10 staff and employees of CV Pena Persada. Keywords:  Pena publisher, Digital Marketing, Internet ABSTRAKPengabdian kepada masyarakat (PKM) ini berlokasi di penerbit CV Pena Persada yang bertujuan untuk memperkenalkan konsep pemasaran digital pada sistem manajemen pemasaran di CV Pena Persada. Penerbit CV Pena Persada memiliki masalah berupa rendahnya penjualan buku dan kurangnya nya pengelolaan marketing berbasis digital. Manajemen penerbit CV Pena Persada belum bisa memaksimalkan berbagai fitur yang disediakan di era digital. Untuk menyelesaikan persoalan tersebut, tim pengabdian memberikan materi tentang dasar-dasar Digital marketing dan bagaimana mempraktekkannya untuk meningkatkan penjualan buku. Metode yang digunakan dalam kegiatan  ini adalah menggunakan seminar untuk menyampaikan materi tentang digital marketing. Digital marketing merupakan sistem penjualan yang memanfaatkan teknologi digital seperti website, optimalisasi mesin pencarian, digital advertising dan berbagai hal lain yang berkaitan dengan dunia digital. Salah satu teknik yang bisa digunakan dalam internet marketing adalah menggunakan website dan platform online, optimalisasi mesin pencarian, dan iklan berbayar digital seperti pada Google AdSense. Hasil dari PKM ini adalah 80% dari staf dan karyawan di penerbit Persada memiliki pengetahuan yang memadai tentang Digital marketing. Selain itu, 90 % peserta juga menyatakan bahwa mereka merasa puas atas materi yang disampaikan. Seminar ini dihadiri oleh staf dan karyawan CV Pena Persada sebanyak 10 orang. Kata Kunci: Penerbit Pena, Digital Marketing, Internet